La Roya del café en Costa Rica: Epidemias, innovación y medio ambiente, 1950-1995 - McCook, Stuart (Revista de historia., 2009)
The history of tropical crops in the second half of the twentieth century is, in large part, a history of innovation. An analysis of this history of innovation allows us to glimpse the environmental history of these crops. Much of the innovation in this period was done to counter an unprecedented wave of crop diseases and pests. Recovering the history of these diseases, in turn, allows us to understand the increasingly fragile ecology of the main crops in Central America. This article analyzes these themes through a history of the coffee rust - Hemileia vastatrix- in Central America, with particular emphasis on Costa Rica.